Infrared thermography to assess dermatomal levels of labor epidural analgesia with 1 mg/mL ropivacaine plus 0.5 µg/mL sufentanil: a prospective cohort study. (February 2020) - Bouvet, L.; Roukhomovsky, M.; Desgranges, F.-P.; Allaouchiche, B.; Chassard, D.
Highlights: Effectiveness of obstetric epidural analgesia is sometimes difficult to assess. Change in skin temperature reflects the sympathetic activity of the cutaneous area. We found that obstetric epidural analgesia led to change in skin temperature. Thermography could be used for objective assessment of spread of epidural analgesia. Abstract: Background: Assessment of the effectiveness of obstetric epidural analgesia may be difficult and techniques for objective assessment of epidural spread of local anesthetic would be useful. In this prospective cohort study we assessed whether obstetric epidural analgesia from a low concentration of ropivacaine led to significant change in cutaneous temperature, related to sympathetic block detected by infrared thermography, at dermatomes C4, T4, T10, L2 and L5. Methods: Women in spontaneous labor who requested epidural analgesia were consecutively recruited. Epidural analgesia was induced with a bolus of 10–15 mL of ropivacaine 1 mg/mL and sufentanil 0.5 µg/mL, followed by continuous epidural infusion. Skin temperature was measured using thermography before and 20 min after the epidural bolus. The verbal pain score using a numeric rating scale was recorded before and 60 min after the epidural bolus. The upper sensory block to cold sensation was tested 30 and 60 min after the bolus by a physician blinded to the skin temperature. Failed epidural analgesia was defined as verbal pain score >3 at 60 min. Results: Fifty-three parturients were included and analyzed. We found a significant increase in skin temperatures measured at T4, T10, L2 and L5 dermatomes, but not at C4, and a significant difference in the change in skin temperature at T10 between failed (n=3) and successful (n=50) epidural analgesia. Conclusions: These results suggest that infrared thermography might be useful for the early diagnosis of successful obstetric epidural analgesia.